Pendampingan Penguasaan Aplikasi Website dan Sistem PPDB Online - Syafiih, M; Syahroni, Muhammad; Mustofa, Zainul; Rohman, Sufi; Asykuri, Muhammad Ilfan (Insan Kreasi Media, 2024)
The Islamic Education Foundation faced serious challenges in IT infrastructure, which led to a lack of access to information as well as a new student admission process that was still done manually. This condition not only hampers administrative efficiency, but also reduces the interest of prospective students to register. To overcome these problems, the development of an official website and online PPDB system is a strategic step that aims to increase transparency and accessibility of information. A Participatory Action Research (PAR) approach, which involves the active participation of the entire service team in problem identification to solution implementation, was used to ensure the success of the project. The results of the programme showed significant improvements in administrative efficiency. The developed website serves as an effective information platform, while the online new student database system speeds up and simplifies the registration process. Training for staff and students also improved their IT skills, which had a positive impact on social change within the organisation. The application of technology in this educational context proved crucial in improving service quality and operational efficiency, making this programme a model that can be adopted by other educational institutions facing similar challenges in the digital age.